Local Fractional Laplace Variational Iteration Method for Fractal Vehicular Traffic Flow - Yang Li; Long-Fei Wang; Sheng-Da Zeng; Yang Zhao (Advances in Mathematical Physics)
We discuss the line partial differential equations arising in fractal vehicular traffic flow. The nondifferentiable approximate solutions are obtained by using the local fractional Laplace variational iteration method, which is the coupling method of local fractional variational iteration method and Laplace transform. The obtained results show the efficiency and accuracy of implements of the present method.